2022
DOI: 10.3390/agronomy12112882
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Weeds and Apple Trees to Beneficial Soil Microorganisms and Mineral Fertilizers Applied in Orchards

Abstract: The effect of beneficial soil fungi, bacteria and mineral fertilizers containing nitrogen, phosphorus and potassium on the level and species composition of weed infestation, uptake of macronutrients by weeds and the nutritional status of ‘Sampion’ apple trees with nitrogen (N), phosphorus (P), potassium (K), magnesium (Mg) and calcium (Ca) was assessed in three-year studies. In the field experiment, the effect of thirteen treatments was investigated, where fungal or bacterial inocula and mineral fertilizers at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Microbial diversity indices were used to reflect species richness and taxonomic proportions across biomes [28]. It was found that the submerged environment would reduce the proportion of fungi and lead to significant changes in the diversity of microbial community structure [29,30]. In our study, it was found that the fungal diversity of HYHE and SHY treatments was significantly higher than that of CK and FP treatments, indicating that the fungal diversity was higher than that of the submerged treatments under alternating dry and wet irrigation.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial diversity indices were used to reflect species richness and taxonomic proportions across biomes [28]. It was found that the submerged environment would reduce the proportion of fungi and lead to significant changes in the diversity of microbial community structure [29,30]. In our study, it was found that the fungal diversity of HYHE and SHY treatments was significantly higher than that of CK and FP treatments, indicating that the fungal diversity was higher than that of the submerged treatments under alternating dry and wet irrigation.…”
Section: Discussionmentioning
confidence: 99%